Navigating the Complexity of Regional Ocean Governance Through the Large Marine Ecosystems Approach - Degger, Natalie; Hudson, Andrew; Mamaev, Vladimir; Hamid, Mish; Trumbic, Ivica (Frontiers in Marine Science, 2021)
Governance is a multifaceted and complex process, involving a wide range of stakeholders from numerous institutions and individuals with different interests, agendas and sets of skills. A number of barriers exist for states to work together on securing their shared coastal and marine ecosystems, with discussions often becoming clouded when disputes arise over Exclusive Economic Zones, borders, oil and gas resources, continental shelves, maritime transport, and fisheries. Over the last thirty-six years, the Global Environment Facility’s (GEF) International Waters focal area has utilized the Large Marine Ecosystem (LME) approach to navigate the complex problems related to transboundary issues affecting the world’s marine ecosystems, of which forty-one out of sixty-six are shared (62%) by one or more countries. To overcome the disputes and assumptions about the intentions of neighbouring states, the GEF developed the Transboundary Diagnostic Analysis-Strategic Action Programme (TDA-SAP) assessment and strategic planning processes to help countries learn how to work together and build trust. This formal and inclusive process analyses all pertinent factual and scientific information to set priorities for action. This practical method for integrating science into management has provided an effective approach to inform and advance sustainable LME management and governance regimes; however, there is not a one size fits all approach. This review presents six examples from the GEF International Waters portfolio that demonstrate how the LME Approach and TDA-SAP process have helped countries find the best way to mainstream ecosystem-based management approaches into existing contexts and politics. While these examples span a wide range of different contexts (geographic, political, socio-economic, temporal), they have all applied the LME Approach and TDA-SAP process to tackle complex regional ocean governance issues. Each example provides a historical perspective, the key results achieved, and their unique lessons learned/best practices. Furthermore, the review identifies some of the overall shortcomings of the process and the common lessons learned, underscoring the complex and daunting challenge of achieving effective governance for multi-country LMEs. The experience provided by these examples shows that practical ecosystem-based management of the ocean and its coasts not only requires flexibility and adaptability, but also time, associated long-term vision and commitment.